Strategi Tokoh Agama Dan Masyarakat Dalam Meminimalisasi Kenakalan Remaja Di Desa Toman Kecamatan Babat Toman Kabupaten Musi Banyuasin - Sri Khojijah; Candra Darmawan; Anang Walian (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: Juvenile delinquency is becoming a serious and complex issue in today's modern society. Juvenile delinquency can involve a variety of negative behaviors such as drug abuse, violent acts, risky sexual behavior, as well as involvement in criminal activities. Therefore, the role of religious and community leaders in minimizing juvenile delinquency is very important. This study aims to determine the factors that cause juvenile delinquency and the strategies of religious and community leaders in minimizing juvenile delinquency in Toman Village, Babat Toman District, Musi Banyuasin Regency. In this study, descriptive research was used sourced from primary data and secondary data. To obtain data, observations, interviews and documentation were carried out after which qualitative analysis was carried out. The results showed that the factors that cause juvenile delinquency in Toman Village, Babat Toman District, Musi Banyuasin Regency, are external and internal factors. The internal factors come from the teenagers themselves while external factors come from family factors, social factors and environmental factors and the strategies of religious and community leaders in minimizing juvenile delinquency in Toman Village, Babat Toman District, Musi Banyuasin Regency can be divided into 3 parts, namely a) village head strategy to minimize juvenile delinquency by taking preventive and curative actions, b) community leaders' strategy to minimize juvenile delinquency by conducting socialization on juvenile delinquency and involving adolescents in social service activities and community service, c) religious leaders' strategy to minimize juvenile delinquency by reviving mosque teenagers and conducting regular weekly public studies held at mosques. KEYWORDS: Strategy, Religious Leaders, Community Leaders, Juvenile Delinquency.